Protectionism and industry localization in Chinese provinces - Cecile Batisse; Sandra Poncet (European Regional Science Association (ERSA), 2003)
This paper investigates the determinants of regional specialization between 1992 and 1997 using a panel covering 33 industries across 25 Chinese regions, paying particular attention to the role of regional protectionism. This study is motivated by a double paradox concerning the Chinese economy over the reforms. First some authors evidence reduced regional specialization despite the promotion of liberalization away from the introverted development strategy of the pre-reform period. Moreover, several empirical works find a negative impact of the degree of regional concentration on the performance of industries. These counter-intuitive findings lead us to evaluate whether the localization of industries in Chinese regions is rooted in a market process or on the opposite results from industrial and trade policies disconnected from the logic of comparative advantages. This article investigates in a straightforward manner the role of inter-provincial barriers to trade in shaping regional specialization. China's economic reforms since 1978 have introduced fiscal decentralization, which provided the local governments with a strong incentive to protect their tax base by shielding local firms and industries from outside competition. We study how the impediments to trade between Chinese provinces impact geographic concentration in production beside other traditional factors such as resource endowment, external economies and increasing returns to scale. Regional protectionism is apprehended through all-inclusive indicators of provincial industry-level trade barriers computed based on inter-provincial trade flows. Regional specialization is measured by a location quotient with respect to output. It is found that the dynamics of comparative advantages and the forces of the new geographic economy are at work in Chinese provinces. It is found that there is greater geographic concentration in industries that enjoy significant knowledge spillovers, specialized suppliers and labor-market pooling. Results however lend strong support to the role of local protectionism on the concentration of activities. The localization of economic activities in Chinese provinces does not exclusively follow the logic of the market. It is also is influenced by interregional trade barriers put in place by local governments. Greater location quotients are found for industries that enjoy high protection from interregional competition. The role of protectionism in regional specialization appears to have increased between 1992 and 1997, especially in the provinces that are the least opened to the international.
Keywords: 330